Efektivitas Pembinaan Keagamaan Islam Di Kampung Skouw Sae Distrik Muara Tami Perbatasan RI-PNG - Nurjanah, Neneng Tuti; Haryani, Lani (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
Religious development in the region is considered not able to strengthen the religious aspects of the people of SkouwSae village. Where is the ceremonially loved by the community, but for the obligatory thing for a Muslim, that relates to worship is forgotten. One example for instance for Jumat prayer worship, only done by a maximum of 15 people who do it in the mosque. The religious coaching Model in the village of SkouwSae has temporary properties, no careful planning, coaching is not done intensively so the benefits are not as thorough. The religious development undertaken by the religious institutions has no variation so that it is felt by the community something boring, and the religious institutions do not lose the field of energy that has a reliable religious knowledge in providing coaching. Lack of religious institutions in conducting coaching in the region. People in the village of SkouwSae are more interested in activities that are ceremonial than this principle because of the ceremonial activities are able to unite the citizens. Ceremonial activities are liked by the citizens because of the lack of coaching that is able to provide motivation to the citizens so that the construction can be felt beneficial to the people of SkouwSae.